BENTUK ORTOGRAFI ISTILAH SERAPAN BAHASA INGGRIS KE DALAM BAHASA ARAB - Suhandano, Rika Astari, Syamsul Hadi, Soepomo Pudjosudarmo, dan (Sekolah Pascasarjana UGM, 2014)
This article aimed to analyze the orthographic form of English loan- terms into Arabic fonotaktik. thescope of the consonant grapheme. It is a kind of descriptive qualitative study, which tends to analyzethe data inductively. Both distributional method and identity method were used for analyzing the data.The result of this study shows that English loan terms denoted in Arabic consists of a symbol graphemesconditional and unconditional symbol. In general, English loan terms into Arabic in accordance withfonotaktik Arabic, but not in substitution the conditional grapheme. It was found that there are stillsome Arabic word forming from English which are not appropriate with the Arabic structures andsystems because of several reasons: (1) a single grapheme of English loan-terms is adapted to manygraphemes; (2) a single grapheme of English loan- terms could symbolize many phonemes; (3) someEnglish terms loan-terms had the phonotactical forms which could not be found in Arabic language,such as words that consist of more than one consonant. The research therefore suggested the consonantschanges which determined by Majma âLughah